Association between blood lead level and risk of stroke in Korean adults: a cross-sectional study in the Korea National Health and Nutrition Examination Survey 2008–2013 - Minkyeong Kim; Sang-Moon Yun; Jihyun Jeong; Chulman Jo; Young Ho Koh (BMJ Open)
Objectives Although lead is a potential risk factor for cardiovascular diseases such as stroke, research on this association in the Korean population remains limited. Therefore, we aimed to investigate the association between lead level and stroke in Korean adults.Design A population-based cross-sectional study.Setting The Korea National Health and Nutrition Examination Survey 2008–2013, which enrolled a representative sample of the Korean population.Participants We excluded participants younger than 20 years, missing weight data, pregnant or lactating, and missing blood lead and stroke data. A total of 11 510 participants were included in this analysis.Primary and secondary outcome measurement The participants were classified by blood lead concentration into the low-level (≤2.189 µg/dL, n=5756) and high-level (>2.189 µg/dL, n=5754) groups. The main outcome, stroke, was assessed by information from physician diagnosis, prevalence of stroke or treatment for stroke. The ORs and 95% CIs were calculated to evaluate the association between blood lead level and stroke using multivariate logistic regression analysis.Results Although blood lead level was not significantly associated with stroke (OR: 1.30, 95% CI: 0.66–2.58) in the multivariate-adjusted model, in individuals with hypertension, the high-level group was 2.36-fold higher odds of stroke (OR: 2.36, 95% CI: 1.02–5.44) compared to that in the low-level group. No association was observed in individuals with normotension (OR: 0.42, 95% CI: 0.13–1.38, p for interaction=0.007).Conclusion The association between blood lead concentration and stroke may be influenced by hypertension status. Our findings suggest the need for closer attention to lead exposure in patients with hypertension.